Students’ engagement in school and peer relations: A literature review - Veiga, Feliciano (2015)
Students' engagement in school (SES) has been studied regarding its relationship with students’ academic achievement and outcomes, as well as with school dropout and behaviour. Literature indicates a general agreement regarding the multidimensional nature of this construct, encompassing two to four dimensions - cognitive, affective,behavioural and personal agency (Fredricks et al., 2004; Glanville & Wildhagen, 2007) likely to predict several outcomes and be influenced by personal and contextual variables. As an element of students’ socio-relational context peer group assumes particular relevance concerning school matters, particularly during adolescence, despite the lack of research on this relation (Furrer & Skinner, 2003; Lynch, Lerner, & Leventhal, 2013; You, 2011), compared to family. In order to describe the state of art of student’s engagement in school and peer relations, we prepared a narrative review. It is assumed that a positive relationship with peers contributes to a sense of belonging to school, which, in turn, promotes the adoption of socially valued goals (Connell & Wellborn, 1991). This paper reviews the literature on the relation between students’ engagement in school and peer relations.